Nursing planning for hospital discharge of patients with heart failure: integrative review (Research, Society and Development, 2022)
The objective of this review is to identify the evidence available in the literature on the role/participation of nursing in the development of a discharge plan for patients with HF to support a master's thesis that proposes to build and validate a discharge plan for patients with HF, based on Orem's Self-Care Deficit Theory and Nursing Interventions Classification (NIC). The research question that guided the investigation was: What evidence is available in the literature on the role/participation of nursing in the development of a discharge plan for patients with HF? The review was carried out from June to August 2020. With the initial search in the databases, it was possible to identify 84 primary articles, 19 in SCOPUS, 15 in PubMed, 15 in LILACS, 12 in EmBase, 12 in BDENF, 06 in CINHAL and 05 in Web of Science. After reading the title and abstract, it was possible to exclude 42 studies, leaving only 21 for full reading. After this step, 09 articles remained in the final sample. The studies analyzed in this review show the importance of nursing in the discharge process of patients with HF, and it is possible to identify possible ways of acting such as: use of an alert card and personal educational health file, health education on adherence to therapy drug and non-drug, instigating the involvement of the patient and family as fundamental tools to reduce the number of hospital readmissions.